Sustainable Manufacturing Practices Adopted by Selected Manufacturing Firms for Sustainable Development in South-East Nigeria - Wogu; Igwe; Nwankwo; Elendu (Journal of Research in Industrial Technology and Educational Studies, 2026)
The study explored the extent sustainable manufacturing practices are adopted by selected manufacturing firms for sustainable development in South-East, Nigeria. Three research questions and three null hypotheses guided the study and descriptive survey research design was adopted by the researchers. The population consisted of 186 managers and 742 employees of selected pharmaceutical, food and beverages and automobiles firms operating in South-East, Nigeria. A sample size of 387 (127 managers and 260 employees) of selected pharmaceutical, food and beverages and automobiles firms operating in South-East, Nigeria was selected for the study using Taro Yamane formula. The instrument for data collection was validated by three experts and the reliability was established using Cronbach alpha statistic which yielded a coefficient of 0.78. Mean and standard deviation were used to answer the research questions while Analysis of Variance was used to test the null hypotheses at 0.05 level of significance. Findings of the study revealed that manufacturing firms adopt sustainable manufacturing practices for sustainable development at a low extent in South-East, Nigeria. Furthermore, the outcome of the study revealed that staff of pharmaceutical, food and beverages and automobiles firms did not differ significantly in their mean ratings on extent to which sustainable manufacturing practices are adopted for sustainable development in South-East, Nigeria. The study concluded that manufacturing industries in South-East, Nigeria are not actively integrating sustainable manufacturing practices into their operations and positioning themselves for sustained success that aligns with global sustainability goals and regulatory standards. Among others, it was recommended that Federal, State and Local Government should strengthen the regulatory framework with clear guidelines, regular inspections, and stricter penalties for non-compliance in order to encourage manufacturing industries in South-East, Nigeria to adopt sustainable manufacturing practices in their operational activities.